Digitalisation in Europe 2020-2021 - Ficarra, Matteo (European Investment Bank, 2021)
Taking an early lead on digitalisation is crucial to Europe's lasting competitiveness. Our newest digitalisation report sheds light on the state of digitalisation in European countries: The adoption of digital technologies by firms in the European Union is improving, but it has not yet closed the gap with the United States; While some EU countries are at the global forefront of digital transformation, others risk being left behind. Digitalisation provides a unique opportunity to improve European firms' global competitiveness. To close the digital divide, Europe needs to increase investment and to create ecosystems that support innovation.